2014
DOI: 10.3389/fgene.2014.00082
|View full text |Cite
|
Sign up to set email alerts
|

SDS, a structural disruption score for assessment of missense variant deleteriousness

Abstract: We have developed a novel structure-based evaluation for missense variants that explicitly models protein structure and amino acid properties to predict the likelihood that a variant disrupts protein function. A structural disruption score (SDS) is introduced as a measure to depict the likelihood that a case variant is functional. The score is constructed using characteristics that distinguish between causal and neutral variants within a group of proteins. The SDS score is correlated with standard sequence-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…Later methods used this information to help calculate basic potentials, low-order and high-order coupling terms, volume terms, and solvent accessibility terms for comprehensive scoring functions that can be weighted through training with machine learning techniques61 or direct fitting to empirical data 63,65. Other structural components that are taken into account include small-molecule binding sites, protein–protein interactions, entropy optimization, and Van der Waals and torsional clashes 63,66…”
Section: Predicting Snv Impactmentioning
confidence: 99%
See 2 more Smart Citations
“…Later methods used this information to help calculate basic potentials, low-order and high-order coupling terms, volume terms, and solvent accessibility terms for comprehensive scoring functions that can be weighted through training with machine learning techniques61 or direct fitting to empirical data 63,65. Other structural components that are taken into account include small-molecule binding sites, protein–protein interactions, entropy optimization, and Van der Waals and torsional clashes 63,66…”
Section: Predicting Snv Impactmentioning
confidence: 99%
“…For example, in a recent study on epilepsy disorders66 only 18/68 of the proteins of interest had partial structures. For the remaining proteins, only 22% of the mutations could be mapped onto a predicted structure from theoretical models based on homology of known structures 66. For a larger perspective, only 7.6% of 57,525 nsSNVs from the Humsavar database could be mapped to structures 74.…”
Section: Predicting Snv Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…Although in silico analysis may be a helpful tool to guide and improve variant interpretation, more specific communication of information used in these programs, such as conservation and the nature of the substituting residue, can be informative because the programs are not vetted for clinical use and have recognized short-comings. 19,20 The next generation of such tools, like Structural Disruption Score (SDS), 21 that predict the protein consequence of a particular nucleotide variation may provide more generalizable outcomes but do need to be validated against existing variant and clinical databases. When our understanding of the molecular blueprint of unique gene families is translated into a computational algorithm that includes the extant knowledge from large, accurate genotype-phenotype databases, the proportion of true VUSs will diminish.…”
Section: Discussionmentioning
confidence: 99%
“…However, these tools have moderate sensitivity and low specificity -one study found that 31-32 % of pathogenic variants were predicted to be benign, while 84-87 % of benign variants were predicted to be pathogenic (Flanagan et al 2010;Dorfman et al 2010). More accurate assessments may be gained by considering each variant in the context of the three-dimensional structure of the protein (Venselaar et al 2013;Preeprem and Gibson 2014).…”
Section: Interpreting the Relevance Of Genetic Variation To Phenotypimentioning
confidence: 99%